Computers [1999 technology forecast and analysis]. - Dutta-Roya, A.
This paper presents a computer technology analysis and forecast for 1999. The subjects covered include personal computers, magnetic disk storage, open operating systems, digital versatile disks and supercomputers
Keywords: Computer technology; Digital versatile disks; Magnetic disk storage; Open operating systems; Personal computers; Supercomputers; Technology analysis; Technology forecast